Automatic Water Flow-Based Soil Moisture Monitoring System Oil Palm Nurseries - Dani, Dani Kurniawan (International Journal of Oil Palm, 2025)
There are many challenges and obstacles that often arise when caring for agricultural crops until harvest time arrives. One of the challenges in caring for oil palm seedlings is controlling soil moisture and maintaining the right water content for the seedlings. Many seedlings die because they do not get enough water, and sometimes extreme weather conditions make it impossible to water the plants. Farmers typically do not have the time to regularly monitor soil moisture and irrigation, especially for large areas. Based on this issue, there is a solution in the form of a soil moisture monitoring system with automatic irrigation based on the Internet of Things (IoT) to assist and simplify the management of these challenges. This study aims to design a soil moisture monitoring system with automatic irrigasstion to help farmers maintain soil moisture in seedbeds. This study uses the Research and Development (R&D) method to develop the previous system as a solution to the problem and improve the previous device. The result of this study is a prototype of an automatic irrigation-based soil moisture monitoring system with a DHT11 sensor and a soil moisture sensor. This system was tested based on calibration results showing that the sensor works with a regression equation. The coefficient of determination obtained for the DHT11 sensor was 0.95 and 0.89, for the soil moisture sensor was 0.91, and for the ultrasonic sensor was 1.0. Based on the regression equation obtained, the system can respond well to changes in temperature, humidity, and water levels to monitor soil moisture in seedbeds.